Réponses

2013-10-10T20:09:54+02:00
A) (9x²-6x+1)-(4x²+4x+1)
   9x²-6x+1-4x²-4x-1
     5x²-10x
b) (x²+8x+16)-(4x²-24x+36)
   x²+8x+16-4x²+24x-36
   -3x²+32x-20
d)4(x²+4x+4)-9(4x²-4x+1)
   4x²+16x+16-36x²+36x-9
   -32x²+52x+7
c) je n'ai pas compris ton énoncé
2013-10-10T20:13:51+02:00
A) (3x - 1)² - (2x +1)² =9x²-6x+1-(4x²+4x+1)=9x²-6x+1-4x²-4x-1=5x²-10x
b) (x + 4)² - (2x -6)²  =x²+8x+16-(4x²-24x+36)=x²+8x+16-4x²+24x-36= -3x²+32x-20
c) (-2x + 3)² - \frac{1}{4}x²  =4x²-12x+9- \frac{1}{16} } =4x²-12x+ \frac{144-1}{16} =4x²-12x+ \frac{143}{16}
d) 4(x + 2)² - 9(2x - 1)² =4(x²+4x+4)-9(4x²-4x+1)=4x²+16x+16-36x²+36x-9= -32x²+52x+7